Distribution of transforming growth factor-beta isoforms TGF-beta 1, TGF-beta 2 and TGF-beta 3 and vascular endothelial growth factor in vulvar lichen sclerosus. - Farrell, A; Dean, D; Charnock, M; Wojnarowska, F (2001)
OBJECTIVE: To study the distribution of transforming growth factor beta (TGF-beta) isoforms TGF-beta 1, TGF-beta 2 and TGF-beta 3 and vascular endothelial growth factor (VEGF) in vulvar lichen sclerosus. STUDY DESIGN: Biopsies were obtained from 10 patients with vulvar lichen sclerosus, snap frozen and stained with polyclonal antibodies to TGF-beta 1, TGF-beta 2, TGF-beta 3 and VEGF. Control tissues used were uninvolved thigh tissue from two of the lichen sclerosus patients and normal vulvar tissue obtained from eight patients during gynecologic procedures. Two specimens of morphea were also examined. RESULTS: Weak TGF-beta 1 staining was demonstrated in the epidermis of all the lichen sclerosus, morphea, thigh and five of the eight normal vulvar specimens. Slight increase in TGF-beta 1 staining was seen in the upper and middermis in 6 of the 10 lichen sclerosus specimens and in the morphea specimens as compared to the control tissue, and this staining was localized within cells. TGF-beta 2 staining was present throughout the epidermis in all the normal thigh, normal vulva, lichen sclerosus and morphea specimens. TGF-beta 2 staining was increased within cells in the upper and middermis of the lichen sclerosus and morphea specimens. TGF-beta 3 staining occurred in the basal half of the epidermis of all the control, lichen sclerosus and morphea specimens, and only slight upper dermal staining of a few individual cells was seen in 3 of the 10 lichen sclerosus specimens. VEGF staining was similar in the normal tissues, lichen sclerosus and morphea. CONCLUSION: These results suggest that TGF-beta may.